Profiling cardiovascular viral pathogens in cases of sudden and unexpected death in infants (SUDI) at the Tygerberg Medico-legal Mortuary and the role of myocarditis as a possible cause of death - Venter, Michaela Lucienne (Stellenbosch : Stellenbosch University., 2020)
Thesis (MSc)--Stellenbosch University, 2020.